A Cross-Country Analysis of the Risk Factors for Depression at the Micro and Macro Level - Natalia Melgar; Maximo Rossi (Inter-American Development Bank (IDB), 2010)
Past research has provided evidence of the role of some personal characteristics as risk factors for depression. However, few studies have examined jointly their specific impact and whether country characteristics change the probability of being depressed. In general, this is due to the use of single-country databases. The aim of this paper is to extend previous findings by employing a much larger dataset and including the country effects mentioned above. The paper estimates probit models with country effects and explores linkages between specific environmental factors and depression using data from the 2007 Gallup Public Opinion Poll. Findings indicate that depression is positively related to being a woman, adulthood, divorce, widowhood, unemployment and low income. Moreover, there is evidence of the significant positive association between inequality and depression, especially for those living in urban areas. Finally, some populations characteristics facilitate depression (age distribution and religious affiliation).
Keywords: D01; I10; I12; J18; Z13; 330; Depression; Health; Well-being; Cross-country research